Bulk Single Crystal‐Like Structural and Magnetic Characteristics of Epitaxial Spinel Ferrite Thin Films with Elimination of Antiphase Boundaries. Issue 30 (12th June 2017) - Singh, Amit V.; Khodadadi, Behrouz; Mohammadi, Jamileh Beik; Keshavarz, Sahar; Mewes, Tim; Negi, Devendra Singh; Datta, Ranjan; Galazka, Zbigniew; Uecker, Reinhard; Gupta, Arunava
Abstract : Spinel ferrite NiFe2 O4 thin films have been grown on three isostructural substrates, MgAl2 O4, MgGa2 O4, and CoGa2 O4 using pulsed laser deposition. These substrates have lattice mismatches of 3.1%, 0.8%, and 0.2%, respectively, with NiFe2 O4 . As expected, the films grown on MgAl2 O4 substrate show the presence of the antiphase boundary defects. However, no antiphase boundaries (APBs) are observed for films grown on near‐lattice‐matched substrates MgGa2 O4 and CoGa2 O4 . This demonstrates that by using isostructural and lattice‐matched substrates, the formation of APBs can be avoided in NiFe2 O4 thin films. Consequently, static and dynamic magnetic properties comparable with the bulk can be realized. Initial results indicate similar improvements in film quality and magnetic properties due to the elimination of APBs in other members of the spinel ferrite family, such as Fe3 O4 and CoFe2 O4, which have similar crystallographic structure and lattice constants as NiFe2 O4 . Abstract : Antiphase boundary defects in epitaxial nickel ferrite thin films are eliminated by using spinel substrates which have a small lattice mismatch with the films. Consequently, bulk single crystal nickel ferrite‐like magnetic and microwave properties are obtained in the films. Magnetite and cobalt ferrite also show similar improvements in thin film quality and properties.